Bitcoin dalam Persepektif Fiqih Muamalah Kontemporer: Bitcoin in the Perspective of Contemporary Fiqh Muamalah - Ulfah, Nurul; Aningti, Amanda Dwi; Suryani, Suryani; Marfu’ah, Siti; Humaemah, Ratu; Azim, Muhammad Fadli; Setiadi, Rezky Mehta (Al Dzahab, 2025)
Purpose: This research is to understand Bitcoin in the perspective of contemporary muamalah fiqh, find out how contemporary scholars understand bitcoin and analyze whether it is permissible or not from the perspective of contemporary muamalah fiqh. Design/methodology/approach: This research method is included in the quantitative category with a descriptive approach process, where the data collection technique relies on references in the library method as the main source. In other words, the data collection method is obtained from literature, such as articles, online media, books and other sources.  Findings: : The results of this research show that bitcoin as an investment is not permitted because it contains gharar and maysir, and is not recognized as an official medium of exchange. The Indonesian government also does not support bitcoin as an official currency and considers it illegal under the Bank Indonesia Law. Research implications: From the results of this research, it is known that the development of Bitcoin in the Contemporary Prefective Fiqh of Muamalah, namely cryptocurrency, whether Bitcoin or other related cryptocurrencies, is still not accepted in Islamic law. and it could be said that it has not been legally and legitimately accepted in Indonesia.